Bridging the gap between researchers, growers, extension and industry in organic strawberry production - Kalaitzoglou, Konstantinos (2019)
The aim of this research was to investigate how and why the development of a knowledge network between researchers, growers, extension agents and industry impacts the knowledge creation and dissemination in organic agricultural networks. Theoretically, we drew upon the concept of Embeddedness in agro-food networks. Empirically, we relied on a case study research by utilizing multiple sources of data.